Hubungan antara Sikap Kerja dengan Keluhan Nyeri Punggung Bawah pada Pengrajin Wuwung Sengdi Desa Karang Tengah, Weru, Sukoharjo - Luthfi, Kharits Abdullah, Umi Budi Rahayu, SST.FT., M.Kes, Isnaini Herawati, M.Sc (2016)
Zinc wuwung craftsmen working in the working attitude is not ergonomic. During the work of craftsmen wuwung zinc can be in a variety of positions, such as sitting / squatting, standing and bending. Wuwung zinc craftsmen are in a standing position when the zinc raw material selection stage. In a squatting position when measuring and cutting stage zinc. In a standing position while performing the manufacturing stage wuwung with wuwung printing equipment. The position of the working attitude is the position at risk of lower back pain. The purpose of this study was to determine the relationship working attitude with lower back pain in zinc wuwung craftsmen in the village Karangtengah, Weru, Sukoharjo with a sample of 100 respondents. This type of research is observational with cross sectional approach. The statistical test used statistin non parametric Chi-Square. The results showed that there was a relationship with the work attitude of lower back pain in the Village craftsmen zinc wuwung Karangtengah, Weru, Sukoharjo (p count<p value, 0.01<0.05). Suggested for craftsmen wuwung zinc to utilize time off as possible as malakukan stretch for a moment, do sports when he is not working and you should pay attention to the attitude wuwung craftsmen at work and avoid long static postue while working.